Ketidakparalelan Bentuk dalam Kalimat Perincian: - Ririen Ekoyanantiasih (Kantor Bahasa Provinsi Maluku Utara, 2015)
This research’s purpose to describe type of unparallelism in detail sentence. This research use descriptive method that explain parallelism strategy in details sentence in register written language, like Kompas (February–March 2010), Media Indonesia (February-Maret 2010), magazine BPPT (No. LVIII 2000), and LAN (2000). This research showed that be found unparallelisms in detail sentence. Those unparallelisms can be found in word, phare, and clause. Unparallelisms can make sentence uneffective and ungrammatical. In this research, unparallelisms in detail sentence be changed to parallelisms. For arrive parallelism in details sentence, strategy was done with affixation, activation, or passivity in sentence of detail. Thus, analysis teknical use proces morphology and syntax.